Anatomical and functional evidence for trace amines as unique modulators of locomotor function in the mammalian spinal cord - Gozal, Elizabeth A.; O'Neill, Brannan E.; Sawchuk, Michael A.; Zhu, Hong; Halder, Mallika; Chou, Ching-Chieh; Hochman, Shawn (Frontiers in Neural Circuits, 2014)
The trace amines (TAs), tryptamine, tyramine, and β-phenylethylamine, are synthesized from precursor amino acids via aromatic-L-amino acid decarboxylase (AADC). We explored their role in the neuromodulation of neonatal rat spinal cord motor circuits. We first showed that the spinal cord contains the substrates for TA biosynthesis (AADC) and for receptor-mediated actions via trace amine-associated receptors (TAARs) 1 and 4. We next examined the actions of the TAs on motor activity using the in vitro isolated neonatal rat spinal cord. Tyramine and tryptamine most consistently increased motor activity with prominent direct actions on motoneurons. In the presence of N-methyl-D-aspartate, all applied TAs supported expression of a locomotor-like activity (LLA) that was indistinguishable from that ordinarily observed with serotonin, suggesting that the TAs act on common central pattern generating neurons. The TAs also generated distinctive complex rhythms characterized by episodic bouts of LLA. TA actions on locomotor circuits did not require interaction with descending monoaminergic projections since evoked LLA was maintained following block of all Na+-dependent monoamine transporters or the vesicular monoamine transporter. Instead, TA (tryptamine and tyramine) actions depended on intracellular uptake via pentamidine-sensitive Na+-independent membrane transporters. Requirement for intracellular transport is consistent with the TAs having much slower LLA onset than serotonin and for activation of intracellular TAARs. To test for endogenous actions following biosynthesis, we increased intracellular amino acid levels with cycloheximide. LLA emerged and included distinctive TA-like episodic bouts. In summary, we provided anatomical and functional evidence of the TAs as an intrinsic spinal monoaminergic modulatory system capable of promoting recruitment of locomotor circuits independent of the descending monoamines. These actions support their known sympathomimetic function.